Public Punitiveness Towards Individuals with Sexual Convictions in Italy: a Vignette Study - Veggi, Sara (European journal on criminal policy and research, 2024)
Sexual violence is among the offences on which the public has expressed the greatest alarm and punitiveness and towards which more severe norms and restraining measures have been introduced in several countries in recent years. Outside of Anglo-American countries, few studies have been conducted on the factors that influence public judgments about individuals who commit sexual offences. To address this question, we surveyed a sample of 517 individuals from the general population in Italy. Participants were randomly presented with a vignette describing a case of sexual violence that varied according to the socioeconomic profile of the male offender, his involvement in treatment, and the age of the victim. Participants rated their level of agreement on various issues such as rehabilitation, accountability, and community management. Controlling for pre-existing attitudes, participants reported that when the offender was involved in treatment, the risk of re-offending was low, that his release into society could be considered, and that it would not be a problem to have a treated offender as a neighbor (especially if of high socio-economic status). Attribution of responsibility varied depending on the victim. When the victim was a young girl, rather than a woman, the responsibility for the violence was attributed exclusively to the offender. In the case of a young victim, participants overestimated how the rate of sex offending affected the country. Attention is also given to the role of comfort with sexuality in influencing these perceptions. Implications for public policy are discussed.